Demographic and Risk Factors of Intracerebral Hemorrhage Stroke Patients in Dr. Hasan Sadikin General Hospital Bandung in 2007â2016 - Lofissa, Sabrina Putri; Ong, Paulus Anam; Atik, Nur (Althea Medical Journal, 2018)
Background: Intracerebral hemorrhage stroke is a type of stroke which is considered to have a higher mortality risk than ischemic stroke. Preventive programs are needed to minimize stroke cases by reducing the risk factors. This study aimed to identify the demographic and risk factors of intracerebral hemorrhage stroke patients in Dr. Hasan Sadikin General Hospital Bandung in 2007â2016. Methods: This was a descriptive cross sectional study. Data were obtained from Dr. Hasan Sadikin General Hospital medical resume January 2007- December 2016 by total sampling.Â  Subjects of this study were intracerebral hemorrhage stroke patients hospitalized in Dr. Hasan Sadikin General Hospital. The period of study was from August 2016 until May 2017. Variables included in this study were gender, occupation, education level, age; risk factors such as hypertension, dyslipidemia, diabetes mellitus, hyperuricemia, and kidney disease. The collected data were presented in percentage.Results: The highest demographic prevalence in 10 years was in female, non-occupational person, elementary school graduate, and frequently found in the 50-59 age group. The highest risk factor was hypertension, but it slightly decreased from 78.8% in 2007-2008 to 55.3% in 2015-2016, followed by dyslipidemia, diabetes mellitus, hyperuricemia which increased in 2007-2008 and 2015-2016. (Dyslipidemia: from 8.1% to 23.8%; Hyperuricemia: from 2.5% to11.2%; Diabetes Mellitus: from 6.6% to 8.9%).Conclusions: The demographic of intracerebral hemorrhage stroke shows a high prevalence found in females, older age, non-occupational persons, and elementary school graduates. Among the risk factors, hypertension is most likely to happen in ten years.Â